Advancing renewable energy: A quadratic high-efficiency high gain step-up DC/DC converter - Preeti Sharma; Sara Hasanpour; Rajneesh Kumar (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Presenting a new high-gain converter that incorporates a coupled inductor, this paper offers a range of advantages over existing designs. The circuit features a simple structure with two cascade semi-stages, two power switches operating in sync, and a coupled inductor. It provides an extensive output voltage range, ensures continuous input current with minimal ripple, maintains positive output voltage polarity, and follows a standard ground configuration. These features make it well-suited for various applications, particularly in photovoltaic systems. Additionally, the voltage stress across each power switch is significantly lower than that of other boost converters, allowing for the selection of power MOSFETs with reduced drain-source ON resistance to ensure high efficiency. This research presents comprehensive assessments of the steady-state and stress conditions as well as thorough comparisons with other similar converters operating in continuous conduction mode. Theoretical advantages of the proposed circuit design are further reinforced by experimental results obtained from a 200-W step-up 25–370 V arrangement.